Left atrial appendage function in patients with atrial flutter. Issue 3 (September 1997) - Omran, H.; Jung, W.; Rabahieh, R.; MacCarter, D.; Illien, S.; Rang, B.; Hagendorff, A.; Schimpf, R.; Lüderitz, B.
Abstract : OBJECTIVE: To determine whether echocardiographic markers thromboembolic risk differ between patients with pure atrial flutter and patients with atrial flutter and intermittent atrial fibrillation. DESIGN: Patients with atrial flutter were followed up prospectively for 12 months to identify intermittent atrial fibrillation. After the follow up period, transthoracic and multiplane transoesophageal echocardiography were performed to assess left atrial chamber and appendage size, peak emptying velocities, and emptying fraction of the left atrial appendage. The presence of spontaneous echo contrast was also determined. SETTING: Tertiary cardiac care centre. PATIENTS: 20 consecutive patients with atrial flutter; 11 healthy subjects in sinus rhythm served as controls. RESULTS: Intermittent atrial fibrillation was documented in 11 patients by Holter monitoring or surface ECG; atrial fibrillation was not found in the other nine patients. Compared with the patients with pure atrial flutter, patients with atrial flutter and intermittent atrial fibrillation had larger left atrial chamber (mean (SD) 4.5 (0.6) v 3.8 (0.5) cm; 95% confidence interval 0.2 to 1.2; P = 0.01) and appendage areas (6.7 (2.2) v 4.8 (4.9) cm; 95% CI 0.4 to 3.5; P = 0.02), lower left atrial appendage emptying fractions (33 (11)% v 52 (11)%; 95% CI 8 to 29; P = 0.008), and also lower left atrial appendage emptying velocities (0.44 (0.21) v 0.79 (0.27) m/s; 95% CI 0.13 to 0.56; P = 0.005). In addition, a higher incidence of spontaneous echo contrast (11% v 36%) was observed in patients with atrial flutter and intermittent atrial fibrillation. CONCLUSIONS: Left atrial appendage function is depressed and spontaneous echo contrast more frequent in patients with atrial flutter and intermittent atrial fibrillation, as opposed to patients with pure atrial flutter. These data support the concept that patients with atrial flutter and intermittent atrial fibrillation have an increased risk of thromboembolic events and should therefore receive adequate anticoagulant treatment.